Resistência de união de diferentes sistemas adesivos universais: efeito do modo de aplicação e do uso de cross-linker após envelhecimento - Silva, Rafael Coutinho (2018)
The aim has been to evaluate the effect of the application mode and the use of cross-linkers in the bond strength of different universal adhesive systems to dentin with and without thermo-mechanical cycling. Sixty-four molars were used, distributed in 16 groups according to the universal adhesive system (Universal Single Bond – SBU or Universal Clearfil – CLU), the application mode (etch-and-rinse or self-etch), the use of cross-linker (EDC or without cross-linker) and fatigue method (n=10). The fatigued specimens were submitted to thermomechanical cycling (120.000 mechanical cycles, 25N, 5 Hz; 10.000 thermocycling 5-55°C). After fatigue, the specimens were cut to obtain sticks with a bond area of approximately 1 mm2 and submitted to the microtensile test in a universal test machine with a speed of 0.5 mm/min. Afterwards, the data were statistically evaluated for each adhesive (3-way ANOVA and Tukey test) with significance level of 5%. For both adhesives (SBU and CLU), there were statistical differences in bond strength (µTBS) in application mode: etch-and-rinse (SBU-30.87±10.90; CLU-27.25±13.05) > selfetching (SBU-25.47±12.44; CLU-22.18±10.24), cross-linker use EDC (SBU30.61±12.41; CLU-27.93±12.33) > without cross-linker SBU (25.79±11.09; CLU-21.55±10.78). There were statistical differences on µTBS after fatigue only for the CLU adhesive, Fatigue (26.57±12.72) > 24 hours (22.91±10.97). It can be concluded that the conventional application of the universal adhesives and the use of EDC cross-linker promoted increase in µTBS and the fatigue conditions of the samples through thermomechanical cycling promoted µTBS alteration for CLU only.